Myocardial peak systolic velocity-a tool for cardiac screening of HIV-exposed uninfected children. - Martins, Paula; Pires, António; Albuquerque, M. Emanuel; Oliveira-Santos, Manuel; Santos, José; Sena, Cristina; Seiça, Raquel (European Journal of Pediatrics, 2020)
HIV-uninfected children exposed prenatally to the virus and to prophylactic antiretroviral therapy are at an uncertain risk of long-term myocardial dysfunction. This study aimed to analyse the structure and function of their ventricles and to identify potential screening tools for this at-risk population. One hundred and fifteen children (77 exposed vs 38 controls) aged between 2.7 and 16.2 years were included. An echocardiographic study was performed where both ventricles' dimensions and systolic functions were evaluated. In the left ventricle, parameters related to diastolic function were also analysed. Tissue Doppler values were determined in the basal state and after passive leg raising. Serologic analysis of amino-terminal pro-B-type natriuretic peptide (NT-proBNP) was carried out. The two groups had identical ventricular sizes and left ventricular diastolic functions. However, contractility assessed by myocardial peak systolic velocity was significantly inferior in the exposed group. These systolic echocardiographic differences were present despite similar values of NT-proBNP in both groups.Conclusion: HIV-exposed uninfected children may be vulnerable to ventricular systolic dysfunction at long term. Cardiovascular surveillance and periodic monitoring of biventricular function are therefore recommended. Myocardial peak systolic velocity may be a useful screening tool for this purpose.What is Known:• Previous studies on HIV-exposed uninfected children subjected prenatally to antiretroviral therapy have alerted to potential long-term cardiovascular toxicity effects on the left ventricle.What is New:• The study gives new insights on ventricular function and morphology in HIV-exposed uninfected children.• Myocardial peak systolic velocities are significantly inferior in this paediatric sub-group, therefore long-term cardiac surveillance is recommended.